2021
DOI: 10.3892/ol.2021.12874
|View full text |Cite
|
Sign up to set email alerts
|

PD‑1 blockade enhances cytokine‑induced killer cell‑mediated cytotoxicity in B‑cell non‑Hodgkin lymphoma cell lines

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0) License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…CIK cell infusion, combined with DC (Dendritic cells), chemotherapy, or even immune checkpoint inhibitors are used clinically to treat various cancers and have obtained high clinical efficacy in lung cancer, hematologic tumor, and gastric cancer, etc. [ 2 6 ]. While CD3 + CD56 + T cells are recognized as a crucial effector population of CIK cells against tumor cells, the purification of CD56 + cell does not significantly improve the capacity in killing tumor cells compared with CIK cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CIK cell infusion, combined with DC (Dendritic cells), chemotherapy, or even immune checkpoint inhibitors are used clinically to treat various cancers and have obtained high clinical efficacy in lung cancer, hematologic tumor, and gastric cancer, etc. [ 2 6 ]. While CD3 + CD56 + T cells are recognized as a crucial effector population of CIK cells against tumor cells, the purification of CD56 + cell does not significantly improve the capacity in killing tumor cells compared with CIK cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a critical role for the PD-1/PD-L costimulatory pathway in the alpha GalCer-mediated induction of iNKT cell anergy as a possible target for immunotherapies has been discussed [111]. Since PD-L1 expression is a predictive biomarker for CIK cell-based immunotherapy and the PD-1 blockade has been shown to enhance CIK cell cytotoxicity [112], the PD-Ls/NKT/CIK axis needs consideration. In order to delete the effect of Tregs on anti-tumor immunity, pre-administration of depleting anti-CD25 monoclonal antibodies prior to α-GalCer vaccination increased α-GalCer-induced prophylactic anti-tumor function in the GL261 murine glioma model, as mentioned above [106].…”
Section: Preclinical Nkt-mediated Immune Therapy In Glioblastomamentioning
confidence: 99%
“…Biederbick et al recently contributed to raise concerns about synergistic molecular mechanisms of CIK cells by using a combination of anti-CD40 and anti-GITR mAb in the human lymphoma cell lines SU-DHL-4 and Daudi (both CD40-positive) [ 60 ]. More recently, Li et al reported an increase in IFN-γ secretion in B-NHL cell lines treated with CIK alone or with the PD-1 antibody, yet this trend was not observed for PD-L1, raising the question of whether PD-1 and PD-L1 are comparable and interchangeable in the clinical practice [ 61 ].…”
Section: Improving Cik Cell Therapy On Lymphomamentioning
confidence: 99%